Systematic review for deep inspiration breath hold in proton therapy for mediastinal lymphoma: A PTCOG Lymphoma Subcommittee report and recommendations - Patel, Chirayu; Peterson, Jennifer; Aznar, Marianne; Tseng, Yolanda D.; Lester, Scott; Pafundi, Deanna; Flampouri, Stella; Mohindra, Pranshu; Parikh, Rahul R.; Mailhot Vega, Raymond; König, Laila; Plastaras, John P.; et al. (Radiotherapy and oncology, 2022)
Purpose - To systematically review all dosimetric studies investigating the impact of deep inspiration breath hold (DIBH) compared with free breathing (FB) in mediastinal lymphoma patients treated with proton therapy as compared to IMRT (intensity-modulated radiation therapy)-DIBH. - Materials and Methods - We conducted a systematic review in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline using the PubMed database to identify studies of mediastinal lymphoma patients with dosimetric comparisons of proton-FB and/or proton-DIBH with IMRT-DIBH. Parameters included mean heart (MHD), lung (MLD), and breast (MBD) doses, among other parameters. Case reports were excluded. Absolute differences in mean doses>1Gy between comparators were considered to be clinically meaningful. - Results - As of April 2021, eight studies fit these criteria (n=8), with the following comparisons: proton-FB vs IMRT-DIBH (n=5), proton-DIBH vs proton-FB (n=5), and proton-DIBH vs IMRT-DIBH (n=8). When comparing proton-FB with IMRT-DIBH in 5 studies, MHD was reduced with proton-FB in 2 studies, was similar (<1 Gy difference) in 2 studies, and increased in 1 study. On the other hand, MLD and MBD were reduced with proton-FB in 3 and 4 studies, respectively. When comparing proton-DIBH with proton-FB, MHD and MLD were reduced with proton DIBH in 4 and 3 studies, respectively, while MBD remained similar. Compared with IMRT-DIBH in 8 studies, proton-DIBH reduced the MHD in 7 studies and was similar in 1 study. Furthermore, MLD and MBD were reduced with proton-DIBH in 8 and 6 studies respectively. Integral dose was similar between proton-FB and proton-DIBH, and both were substantially lower than IMRT-DIBH. - Conclusion - Accounting for heart, lung, breast, and integral dose, proton therapy (FB or DIBH) was superior to IMRT-DIBH. Proton-DIBH can lower dose to the lungs and heart even further compared with proton-FB, depending on disease location in the mediastinum, and organ-sparing and target coverage priorities.
Online verfügbar 14 Oktober 2022, Artikelversion 3 November 2022
Gesehen am 24.01.2023